A Educação superior no Brasil e o ensino a distância: uma análise crítica do estágio supervisionado - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
We question the Supervised Practice of teacher's educational courses, in distance learning modality, objectifying to understand in what way the Supervised Practice at EaD makes possible the education, based upon the construction of teacher`s autonomy. In this study, our analysis was restricted to the course of History, at University Aberta do Brasil (UAB), executed by University Estadual de Goias (UEG). For that reason, we have observed the AVA of Supervised Practice at UnUEAD History course, applying on-line surveys to pupils and tutors of Alexania and Itumbiara education centers, as well as to the coordinator of the supervised training, and also to the coordinator of UnUEAD History course. Official documents of the course have also been consulted (Pedagogical Political Project, Trainee's Manual, Rules of Procedure of the Supervised Practice at UnUEAD graduation courses, and so on). The reflection on Education at Distance (EaD) in Brazil is justified, taking into consideration this is one of the current modalities of educational politics, which has been receiving important incentives from the State and, in account of that, gaining the adhesion of superior education institutions. UAB Program is constituted by politics directed to teacher's education, and was created by the Ministry of Education and Culture (MEC) and the Forum of the State Agencies, in 2005. Data analysis was based upon dialectical historical materialism, searching to apprehend the historicity of education at distance, the contradictions and the dynamics of the reality, where educational politics in Brazil are developed, in a qualitative perspective. In the context of the herein developed debates on EaD, we reflect on the potentialities and the limits of teacher's education at distance, in a moment marked by the increased growth of the use of the information ixand communication technologies in educational field, as well as by the implantation of neoliberal politics. Under this perspective, EaD was not studied solely, but it dialogues with authors of different theoretical perspectives hereunder presented, who have in common the effort to understand the complexity of teacher's education politics, in the bulge of the contradictions of this society. From the analyses of this study on, we conclude that, in a general way, the conditions presented by supervised practice, at UnUEAD History course, do not favor the construction of the autonomy of the teacher. EaD is organized and based upon the logic of the capital, which prioritizes the formation of unsound mind individuals, and the certification of graduates for the labor market.
Keywords: Educação a distância; Formação de professores; Estágio supervisionado; Education at distance; Teacher training; Supervised practice; CIENCIAS HUMANAS::EDUCACAO